Pazopanib in advanced vascular sarcomas: an EORTC Soft Tissue and Bone Sarcoma Group (STBSG) retrospective analysis. (2nd January 2017) - Kollár, A.; Jones, R. L.; Stacchiotti, S.; Gelderblom, H.; Guida, M.; Grignani, G.; Steeghs, N.; Safwat, A.; Katz, D.; Duffaud, F.; Sleijfer, S.; van der Graaf, W. T.; et al.
Abstract: Background: Pazopanib is a multitargeted tyrosine kinase inhibitor approved for the treatment of patients with selective subtypes of advanced soft tissue sarcoma (STS) who have previously received standard chemotherapy including anthracyclines. Data on the efficacy in vascular sarcomas are limited. The main objective of this study was to investigate the activity of pazopanib in vascular sarcomas. Patients and methods: A retrospective study of patients with advanced vascular sarcomas, including angiosarcoma (AS), epithelioid hemangioendothelioma (HE) and intimal sarcoma (IS) treated with pazopanib in real life practice at EORTC centers as well as patients treated within the EORTC phase II and III clinical trials (62043/62072) was performed. Patient and tumor characteristics were collected. Response was assessed according to RECIST 1.1. and survival analysis was performed. Results: Fifty-two patients were identified, 40 (76.9%), 10 (19.2%) and two (3.8%) with AS, HE and IS, respectively. The response rate was eight (20%), two (20%) and two (100%) in the AS, HE and IS subtypes, respectively. There was no significant difference in response rate between cutaneous and non-cutaneous AS and similarly between radiation-associated and non-radiation-associated AS. Median progression-free survival (PFS) and median overall survival (OS; from commencing pazopanib) were three months (95% CI 2.1–4.4) and 9.9 months (95% CI 6.5–11.3) in AS, respectively. Conclusion: The activity of pazopanib in AS is comparable to its reported activity in other STS subtypes. In this study, the activity of pazopanib was similar in cutaneous/non-cutaneous and in radiation/non-radiation-associated AS. In addition, pazopanib showed promising activity in HE and IS, worthy of further evaluation.